The Comparison of Subtitle Translation of Barbie Movie 2023 Using Google Translate and NiuTrans - Elsa Septia Herlina (Institute of Research and Community Outreach - Petra Christian University, 2025)
This study is a qualitative study in order to compare of subtitle translation of Barbie Movie 2023 using Google Translate and NiuTrans. The objectives of this study are to find out the similarities and differences meaning between two machine translations. This study used Bowker (2023) and Newmark (1988). The data were collected from the subtitle of Barbie movie 2023. The writer found four categories based on meaning from comparing Google Translate and NiuTrans. There are correct, less correct, not correct, and differences meaning translation results. In the findings were found the same translation and different translations between both Google Translate and NiuTrans. Both also have different meanings in translating the source language. In conclusion, machine translation is not always correct, we still need human translators in translating.